PERSONNEL MANAGEMENT IN MEDICAL ORGANIZATIONS: THE OPPORTUNITIES AND PROSPECTS FOR THE USE OF MODERN STAFF TECHNOLOGIES - S. A. Efimenko; N. V. Zaitseva (Сеченовский вестник, 2012)
This article deals with the analysis of the opportunities and prospects for the use of modern staff technologies in medical organizations.